The Impact of a Discourse Technique on Learning Advanced Writing Skills by Jordanian EFL University Students - Al-Sobh , Mahmoud Ali; Al- Zoubi , Samer Mahmoud; Battah, Monther Mohammad (Journal of Ecohumanism, 2024)
The main purpose of this experimental study is to investigate the impact of a discourse technique (DT) on learning advanced writing skills by Jordanian EFL university students. It also aimed to provide university instructors with suitable techniques to help them teach writing and enhance students’ writing proficiency. The participants of the study consist of 40 EFL university students majoring in English language (20 male students and 20 female students) studying advanced writing (Writing 2: Essay Writing) course at the Department of English Language and Literature. The participants were divided into two groups: experimental and control groups. The experimental group was taught using the discourse technique, whereas the control group was taught using the traditional one. To test the significance of the means, the researchers used one-way ANCOVA. The results revealed statistically significant differences between the two groups, in favor of the experimental group for those who were exposed to the training program compared to the control group members. The results also indicated that there were statistically significant differences between the groups according to gender, in favor of female students in the experimental group because they were exposed to the training program. This study provides beneficial insights into using a discourse technique and effective teaching methods to enhance the writing proficiency of EFL students. The study recommended conducting similar studies investigating the impact of the discourse technique on EFL students’ writing skills at other universities in Jordan.